Revised and Extended Analysis of Five Times Ionized Argon (Ar VI) - Raineri, María Mónica (1992)
The spectrum of five times ionized argon, (Ar VI), has been observed in the 280-2100 Å wavelength range. Eighty-seven lines have been identified as transitions between levels of the 3s23p, 3s3p2, 3s23d, 3p3, 3s3p3d, 3s24s, 3s24d and 3s3p4s configurations. For 33 of the lines the classification is new. Forty-one energy level values belonging to these configurations were analyzed and we propose 9 new energy level values for levels corresponding to odd parity configurations. The configurations are interpreted by fitting the theoretical energy expressions to the observed energy levels using least- squares techniques. The parameter values are compared with results from Hartree-Fock calculations.